Exploring a comprehensive review of non-linear and composite phase frequency detectors within PLL frameworks - N.R. Sivaraaj; K.K. Abdul Majeed (Results in Engineering)
This survey presents an in-depth exploration of two innovative designs of phase frequency detectors (PFDs): Non-Linear PFD (NLPFD), composite PFD. PFDs play a crucial role in phase-locked loops (PLLs), frequency synthesis circuits, frequency demodulators, AM radio receivers, etc. This works focuses on measuring the performance parameters such as blind zone, dead zone, detection range, reset delay, number of transistors utilized, power consumption, maximum operating frequency, and area. Through a comprehensive analysis, a light has been shed on the significance of these designs in advancing the capabilities of PLLs and frequency synthesis circuits. In this study also discusses the techniques to mitigate PFD parameters such as dead zone, blind zone. Finally, this paper concludes with the analysis of PLL using LPFD, NLPFD, and composite PFD architectures.